PENGARUH INFLASI, SUKU BUNGA, RETURN ON ASSET (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM - Rizky Apriliany, Rany Dwi; Effendi, Maya Syafriana; Apriliany, Rany Dwi Rizky (Universitas Persada Indonesia YAI, 2019)
ABSTRACTThe purpose of this research is to determine the effect of Inflation, Interest Rate, Return onAssets (ROA) and Debt to Equity Ratio (DER) on Stock Returns on Property and Real EstateCompanies Listed on the Indonesia Stock Exchange for the Period of 2011 to 2016.The number of samples is 29 companies with the purposive sampling method to choosethe samples.This research is using multiple regression analysis technique. Before analyzing theregression results, descriptive statistics, classical assumption tests (the most suitable test arenormality, multicollinearity and heteroscedasticity tests) and coupled test to decide theregression model ( a suitable test is a random effect model).The results shows that based on ANOVA test, Inflation, Interest Rate, Return On Assets(ROA) and Debt to Equity Ratio (DER) together has a significant influence on Stock Returns.The large contribution of Inflation, Interest Rate, Return on Assets (ROA) and Debt to EquityRatio (DER) to Stock Return is 6.6987% and the remaining 93.3013% are affected by anothervariable by another than used on this research